Populism, Political Stability, And The Construction Of Tourism Destination Image In Contemporary Democracies - Elio Marquez Paredes (International Interdisciplinary Business Economics Advancement Journal, 2026)
The relationship between politics and tourism has long been acknowledged in both political science and tourism studies, yet it remains theoretically fragmented and empirically underexplored, particularly in the context of contemporary populism. In recent decades, populist movements and leaders have gained unprecedented power across Western democracies and emerging economies alike, reshaping political institutions, public discourse, and international perceptions of national identity. At the same time, tourism has become one of the most politically sensitive and economically consequential industries, deeply dependent on national image, political stability, and global reputation. This article develops a comprehensive theoretical and empirical synthesis of how populism and political instability interact with destination image formation and tourism competitiveness. Drawing strictly on the multidisciplinary literature provided, the study integrates political theory, particularly the work on populism, hegemony, and state legitimacy, with tourism research on destination image, risk perception, and country branding. The article argues that populism operates as a discursive and institutional force that reshapes how nations are perceived both domestically and internationally, thereby influencing tourism flows, investor confidence, and destination competitiveness. Through a qualitative and interpretive analysis of political discourse, institutional dynamics, and tourism perception frameworks, the study demonstrates that populist governance tends to produce volatile and polarized country images that simultaneously attract and repel different segments of the global tourism market. On the one hand, populist rhetoric may generate visibility, emotional engagement, and symbolic authenticity, potentially appealing to certain tourists seeking cultural or political novelty. On the other hand, populism often amplifies perceptions of political instability, nationalism, and social conflict, which are empirically associated with heightened travel risk perception and declining tourism demand. By synthesizing the political economy of instability with destination image theory and the politics of tourism governance, this article offers a unified conceptual model explaining how political ideology, state legitimacy, media narratives, and tourist psychology interact in the era of populism. The findings have important implications for tourism policymakers, destination marketers, and political leaders, suggesting that sustainable tourism development in the twenty-first century cannot be separated from the quality of democratic governance, institutional stability, and the strategic management of national image.